THE PARADIGM OF ARTIFICIAL INTELLIGENCE (AI) IN INTERPRETING LAW - Oana Andra NIȚĂ (Association of Social and Educational Innovation, 2024)
In the context of fast digital development, the interaction between human beings and artificial intelligence (AI) in the context of law presents a fascinating and evolving landscape. This relationship encompasses various dimensions, including the integration of AI in legal practice, ethical considerations, regulatory challenges, and the broader implications for justice and society. The relationship between men and AI in the context of law is characterized by both opportunities and challenges. While AI has the potential to enhance legal practice, improve access to justice, and streamline processes, it also raises significant ethical, regulatory, and employment considerations. The future of law will depend on effectively integrating AI while preserving fundamental legal principles, ensuring that technology serves to uphold justice and human dignity. Balancing innovation with ethical responsibility will be crucial as the legal profession navigates this evolving landscape.